2005
DOI: 10.1577/m04-189.1
|View full text |Cite
|
Sign up to set email alerts
|

Stock Identification of Walleye via Otolith Chemistry in the Eleven Point River, Arkansas

Abstract: Otolith chemistry was used to identify two hatchery stocks (Missouri State Hatchery and Arkansas Federal Hatchery) and a possible wild stock of walleye Sander vitreus in the Eleven Point River in northeastern Arkansas. Previous population estimates by the Arkansas Game and Fish Commission using traditional tag-and-release techniques failed to identify the relative survival of these stocks or their spatial and temporal persistence. Using chemical analysis of otoliths combined with a priori knowledge of the hatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…Our findings corroborate those of a few other recent studies that demonstrated that otolith microchemistry and isotopic analysis represent powerful techniques for retrospectively describing the environmental history of fishes that reside solely in freshwaters, including lakes (Joukhadar et al 2002;Brazner et al 2004;Munro et al 2005;Ludsin et al 2006), streams (Wells et al 2003), and small rivers (Bickford and Hannigan 2005). The results of this study demonstrate that otolith elemental and isotopic assays can also be applied to gain valuable insight into fish movement between large rivers and associated lentic floodplain habitats that would be difficult to obtain by other means.…”
Section: Relation Between Fish Age and Source Habitat And Implicationsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings corroborate those of a few other recent studies that demonstrated that otolith microchemistry and isotopic analysis represent powerful techniques for retrospectively describing the environmental history of fishes that reside solely in freshwaters, including lakes (Joukhadar et al 2002;Brazner et al 2004;Munro et al 2005;Ludsin et al 2006), streams (Wells et al 2003), and small rivers (Bickford and Hannigan 2005). The results of this study demonstrate that otolith elemental and isotopic assays can also be applied to gain valuable insight into fish movement between large rivers and associated lentic floodplain habitats that would be difficult to obtain by other means.…”
Section: Relation Between Fish Age and Source Habitat And Implicationsupporting
confidence: 90%
“…Strontium concentrations were normalized to Ca concentration based on the consideration of calcium as a pseudointernal standard (Bickford and Hannigan 2005;Ludsin et al 2006); data are reported as Sr:Ca ratios (mmol/mol) for consistency with published otolith microchemistry literature and reflect differences in Sr concentration among samples. Mean limit of detection for 88 Sr was 0.09 lg/g; otolith 88 Sr concentrations ranged from 494 to 6,952 lg/g.…”
Section: Nonnative Centrarchids In the Colorado Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…Otolith elemental concentrations were calculated from integrations over the final 10 s of laser ablation transects, as the outer portion of the otolith reflects a fish's most recent environmental history. Trace element concentrations were normalized to calcium (Ca) concentration based on the consideration of Ca as a pseudointernal standard (Bickford & Hannigan, 2005;Ludsin et al, 2006); data are reported as element:Ca ratios (mmol/mol).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most critical components to recovery of an endangered fish is that reproduction results in successful recruitment of young into the adult spawning population (NCR 1995;Budy and Schaller 2007 (Campana 1999, Elsdon et al 2008, and along with daily accretions of aragonite, trace elements with a similar charge to calcium are substituted for calcium during crystallization (Bickford and Hannigan 2005). Trace elements are incorporated into the crystalline matrix in proportion to their abundance in the ambient water (Elsdon et al 2008;Pangle et al 2010).…”
Section: List Of Tablesmentioning
confidence: 99%